LATEST INNOVATIONS IN ANIMAL DEPARTMENT WELCOME TO THE ERA OF TECHNOLOGY AND SUSTAINABILITY - Zulkifli, Zulkifli (PT. Antis International Publisher, 2024)
Rapid developments in technology and the need for environmental sustainability have driven significant innovation in animal husbandry. This research examines the latest innovations in the livestock sector that integrate the latest technology and sustainability principles. The main focus of this research is on three main aspects: information and communication technology (ICT) in livestock management, environmentally friendly livestock rearing techniques, and efficient resource management strategies. First, the application of ICT, such as the Internet of Things (IoT) and data analytics, enables real-time monitoring and management of livestock health and productivity. This system reduces the need for manual labor and increases accuracy in decision making. Second, innovations in livestock rearing techniques include the use of organic waste-based feed and waste management systems that reduce environmental impacts and increase the efficiency of resource use. Third, the sustainability approach includes land and water management methods that reduce erosion and pollution, as well as the integration of sustainable agriculture in livestock practices. This research uses qualitative analysis methods with case studies and secondary data from the latest literature to evaluate the impact and effectiveness of this innovation. The results show that the integration of technology and sustainability principles not only increases productivity and efficiency, but also contributes to reducing negative impacts on the environment. These findings provide valuable insights for the development of livestock education curricula and industrial policies that support more innovative and environmentally friendly livestock practices.